Pediatric training and practice of Canadian chiropractic and naturopathic doctors: a 2004–2014 comparative study - Porcino, Antony (BMC Complement Altern Med, 2017)
BACKGROUND: To assess chiropractic (DC) and naturopathic doctors’ (ND) knowledge, attitudes, and behaviour with respect to the pediatric patients in their practice. METHODS: Cross-sectional surveys were developed in collaboration with DC and ND educators. Surveys were sent to randomly selected DCs and NDs in Ontario, Canada in 2004, and a national online survey was conducted in 2014. Data were analyzed using descriptive statistics, t-tests, non-parametric tests, and linear regression. RESULTS: Response rates for DCs were n = 172 (34%) in 2004, n = 553 (15.5%) in 2014, and for NDs, n = 171 (36%) in 2004, n = 162 (7%) in 2014. In 2014, 366 (78.4%) of DCs and 83 (61%) of NDs saw one or more pediatric patients per week. Pediatric training was rated as inadequate by most respondents in both 2004 and 2014, with most respondents (n = 643, 89.9%) seeking post-graduate training by 2014. Respondents’ comfort in treating children and youth is based on experience and post-graduate training. Both DCs and NDs that see children and youth in their practices address a broad array of pediatric health concerns, from well child care and preventative health, to mild and serious illness. CONCLUSIONS: Although the response rate in 2014 is low, the concerns identified a decade earlier remain. The majority of responding DCs and NDs see infants, children, and youth for a variety of health conditions and issues, but self-assess their undergraduate pediatric training as inadequate. We encourage augmented pediatric educational content be included as core curriculum for DCs and NDs and suggest collaboration with institutions/organizations with expertise in pediatric education to facilitate curriculum development, especially in areas that affect patient safety.